The Acute Radiation Syndrome-Mitigator Romiplostim and Secreted Extracellular Vesicles Improved Survival in Mice Acutely Exposed to Myelosuppressive Doses of Ionizing Radiation - Masaru Yamaguchi; Ikuo Kashiwakura (Biomolecules, 2023)
In cases of accidental high-dose total-body irradiation (TBI), acute radiation syndrome (ARS) can cause death. We reported that the thrombopoietin receptor agonist romiplostim (RP) has the potential to completely rescue mice exposed to lethal TBI. Extracellular vesicles (EVs) are involved in cell-to-cell communication, and the mechanism of RP action may be related to EVs that reflect the radio-mitigative information. We investigated the radio-mitigative effects of EVs on mice with severe ARS. C57BL/6 mice exposed to lethal TBI were treated with RP, and the EVs were isolated from the serum and intraperitoneally injected into other mice with severe ARS. The 30-day survival rate of lethal TBI mice drastically improved by 50–100% with the administration of EVs in the sera collected weekly from the mice in which radiation damage was alleviated and mortality was avoided by the administration of RP. Four responsive miRNAs, namely, miR-144-5p, miR-3620-5p, miR-6354, and miR-7686-5p showed significant expression changes in an array analysis. In particular, miR-144-5p was expressed only in the EVs of RP-treated TBI mice. Specific EVs may exist in the circulating blood of mice that escaped mortality with an ARS mitigator, and their membrane surface and endogenous molecules may be the key to the survival of mice with severe ARS.